Analysis of Experimental Works on Improving the Seed Selection Process (International Journal of Scientific Trends, 2023)
This article describes the method of improving the seed sorting device and carrying out experiments in the seed sorting process. As a result, advantages over the existing ones and efficiency gains from its introduction were determined.